Six Recommendations for Youth Sport Stakeholders When Evaluating Their Programs. Issue 3 (2nd July 2020) - Shaikh, Majidullah; Bean, Corliss; Forneris, Tanya
Abstract: Sport stakeholders can drive program improvement using feasible and effective evaluation practices. In this paper, we describe six recommendations to help sport stakeholders integrate evaluation into their practice, including: (a) appraise a program's evaluation capacity, (b) establish partnerships and assemble an evaluation team, (c) evaluate how a program is delivered and a program's outcomes, (d) use practical methods that fit the sport context to produce program-specific findings, (e) empower youth voice, and (f) reflect and revise on an ongoing basis. We hope that these recommendations help sport organizations improve quality program delivery to attain desired outcomes.